Union Campaigning and Coalition Building: The Case of we are Ohio. Issue 4 (30th November 2016) - Thomas Coventry, Barbara; Van Hoy, Jerry
Abstract : The union community organizing approach advocates coalition building between unions and community groups. Union leaders must be educated about social concerns in their community, and union activities and campaigns must serve as a means of educating the community. We examine how union and community groups formed a coalition to repeal Ohio Senate Bill 5/Issue 2, a law restricting collective Bargaining in Ohio. Our article uses interviews and an analysis of newspaper coverage of the Ohio Senate Bill 5/Issue 2 campaign to examine how the campaign to repeal the law met the goal of educating the community to understand the right to collective bargaining as a social justice issue. We identify four interrelated themes in the newspaper coverage of the Senate Bill 5/Issue 2 campaign that unions and their allies used to successfully convince the populace of Ohio to vote for repeal.